Peningkatan Kemampuan Membaca pada Siswa SDN 121/I Muara Singoan Kelas Rendah sebagai Bagian Integral dari Perkembangan Bahasa - Putri, Intan Annidya; Wulandari, Eka; Napizah, Voni (Al-DYAS, 2023)
Reading proficiency is a key competence in language development for children at the primary school level. This study aims to explore the efforts undertaken by SDN 121/I Muara Singoan in improving the reading abilities of elementary school students and understanding its integral role in overall language development. Through a qualitative research approach, data were collected through classroom observations, interviews with teachers, and analysis of curriculum-related documents and teaching strategies. The results of this study indicate that SDN 121/I Muara Singoan has implemented various specific learning strategies to enhance students' reading abilities. Some of these strategies include the use of engaging textbooks, group reading activities, and a library program that expands students' access to reading materials. Additionally, the role of teachers and parents is recognized as a crucial factor in improving students' reading abilities. Teachers provide continuous support through training and guidance, while parents are involved in supporting reading practices at home and providing positive reinforcement. The improvement of reading abilities among lower-grade students at SDN 121/I Muara Singoan has significant impacts on overall language development. In addition to enhancing reading skills, students also demonstrate improvements in content comprehension, critical thinking abilities, and written expression.